ChemInform Abstract: Synthesis of 4‐Phenyl‐5, 6‐dihydrobenzo[h]quinazolines and Their Evaluation as Growth Inhibitors of Carcinoma Cells. Issue 26 (June 2016) - Maurya, Hardesh K.; Hasanain, Mohammad; Singh, Sarita; Sarkar, Jayanta; Dubey, Vijaya; Shukla, Aparna; Luqman, Suaib; Khan, Feroz; Gupta, Atul
Abstract: A cyclization of chalcones with guanidine yields benzo[h]quinazolines which can be easily further converted to compounds (VII) or (IX).